Control of Joint Property by Ex-Husband After Divorce in Banua Kepayang Village, Labuan Amas Selatan Sub-District, Hulu Sungai Tengah District - Hernayanti, Rini; Muhammad Fahmi Nurani (Fakultas Syariah UIN Antasari, 2024)
This research is motivated by the problem of joint property controlled by the former husband after divorce in Banua Kepayang Village, Labuan Amas Selatan District, Hulu Sungai Tengah Regency. In this case, when a divorce occurs, the joint property is controlled by the former husband. It should be based on the Compilation of Islamic Law Article 97 states that